Perbandingan Kelimpahan dan Struktur Komunitas Zooplankton di Pulau Kodingareng dan Lanyukang, Kota Makassar - Hasanah, Alinda Nurbaeti; Rukminasari, Nita; Sitepu, Farida G (Torani Journal of Fisheries and Marine Science, 2014)
This study aimed to determine and compare community structure and assemblages species of zooplankton at Kodingareng and Lanyukang Island. This study used randomly sampling method and the sampling was conducted on July, August and October 2012. Data was analysed using at PRIMER software program. The results showed that zooplankton at Kodingareng and Lanyukang Isla nd had 48 taxa. 47 taxa was found when sampling at dry season and 25 taxa was found when the sampling at wet season. The species was only found at Kodingareng Island were Cypris and Amphipod, while the species was only found at Lanyukang Island was  Luciferidae zoea, Tad  Pole  and  Tintinid.  The  highest  average  of  zooplankton  abundance  was  found  at  dry  season  sampling  at Lanyukang Island, account for 670 individu/L. The result of ANOSIM showed that the level of significance of zooplankton  community  structure  a t  Lanyukang  and  Kodingareng  Island  was  0.5%.  Based  on  nMDS  plot  of zooplankton assemblages species between Lanyukang and Kodingareng Island showed clear seperation. The SIMPER result showed that there was no species seperator of community structure between those islands due to there was the same dominance of species, such as Calanoida, Cyclopoida, dan Chaetognatha.